Impelementasi RI 4.0 Dengan Adopsi Extensible Business Reporting Language (XBRL) dan Pengaruhnya Terhadap Audit Reporting Lag di Bursa Efek Indonesia Tahun 2016-2020 - Zahri Fadli; Jumiadi AW; Devina Ariyani; azizul kholis (Jurnal Riset AKuntansi dan Bisnis, 2022)
This study aims to determine the impact of Extensible Business Reporting Language (XBRL) adoption on Audit Reporting Lag (ARL) in manufacturing companies listed on Indonesia Stock Exchange (IDX) in the 2016 to 2019 period. The total of population in this study were 184 companies with purposive sampling technique, so that a sample of 37 companies was obtained that entered the sampling criteria. This study has two control variables, namely Firm Size (SIZE) and Public Accountant Firm Quality (Big4). The data were analyzed with the F Test and Determinant Test after the data was declared normal with the Normality Test which was processed using the SPSS version 23 application. The results of this study conclude that the adoption of XBRL has a significant effect on ARL in manufacturing companies listed on the IDX. The coefficient of determinant (Adjusted R Square) in this study is 0.022 and after the control variable is entered it becomes 0.103. It means that ARL is influenced by the independent variable and the control variable is 10.3% while the remaining 89.7% is influenced by other factors outside the study.